Mamilov N.Sh., Bekkozhayeva D.K., Amirbekova F.T., Kozhabaeva E.B., Sapargalieva N.S. A checklist of fish species in the Kazakhstan part of the basin of the Chu River: Al-Farabi Kazakh National University, Scientifc Research Institute of Biology and Biotechnology problems, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
Results of investigations of fish diversity in the Kazakhstan part of the Chu watershed are presented.About 34-35 fish species were revealed, 20 species among them were indigenous. Severtsov’s loachTriplophysa sewerzowii (G.Nikolsky, 1938) is a new fish species for the basin. Origin of populations ofspotted thicklip loach Triplophysa strauchii strauchii (Kessler, 1874), plain thicklip loach Triplophysa labiata (Kessler, 1874) and Severtsov’s loach is disputable. The area of indigenous roach, ide, carp, perch,rosy bitterling as well as alien snakehead, rosy bitterling and beautiful sleeper extended in contrast tothe previous reports. On the contrary, tench and Balkash perch were not revealed. Surviving of smallpopulations of barbells, Seven River’s minnow and wels catfish were confirmed. No one finding of Chusharpray was reported during last 30 years, and so this subspecies should be considered as extinct inthe wild (criteria E of the IUCN). Obtained results indicated high value of Kazakhstan part of the Chuwatershed as a hot spot for conservation of diversity of indigenous specific fishes as well as big potentialfor fishery production. Except roach, distribution of all indigenous fishes in the watershed was lace-likeand number of their populations fluctuated deeply. Therefore, fish diversity in every site was much lessthat was indicated in the check list. Reasonable public management of nature of the region should be thebest way to the fish diversity conservation and sustainable use.Key words: Chu River, ichthyofauna, indigenous, alien, diversity